2018
DOI: 10.1111/cpf.12532
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of novel ultrasound equations for estimating percent intramuscular fat

Abstract: The high ICCs and low SEMs suggest that ultrasonography-derived rectus femoris percent fat may be a reliable tool for tracking changes in lower extremity intramuscular adiposity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
(56 reference statements)
4
20
0
Order By: Relevance
“…Results from our study may support the use of US measures of quadriceps morphology, as all observed changes across time points were greater than previously established between-session SEM in RF US (7.1%). 2 Furthermore, we observed similar percentage differences in quadriceps CSA in comparison with previous MRI assessments of muscle volume. For example, Grapar Žargi et al 11 revealed a 17.4% decrease in involved limb quadriceps muscle volume from preoperative to 4 weeks postoperative, while our cohort displayed a 21.5% decrease in CSA at 9 weeks.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Results from our study may support the use of US measures of quadriceps morphology, as all observed changes across time points were greater than previously established between-session SEM in RF US (7.1%). 2 Furthermore, we observed similar percentage differences in quadriceps CSA in comparison with previous MRI assessments of muscle volume. For example, Grapar Žargi et al 11 revealed a 17.4% decrease in involved limb quadriceps muscle volume from preoperative to 4 weeks postoperative, while our cohort displayed a 21.5% decrease in CSA at 9 weeks.…”
Section: Discussionsupporting
confidence: 82%
“…9 Additionally, intersession reliability has been previously established for US assessment of RF CSA and PF (ICC, 0.988 and 0.980, respectively) and standard error of measurement (SEM, 7.01%, and 3.07%, respectively). 2…”
Section: Methodsmentioning
confidence: 99%
“…If raters do not follow the fascia border, they may include the fascia and thus arbitrarily increase CSA and EI; conversely, if they are too conservative, they may miss parts of the muscle. Very often EI is normalized to subcutaneous fat, but where and how each researcher records the depth plays a major role in determining the correct EI values ( 16 ) . All of these integral steps in analyzing US images are a potential place of error in data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we assessed the intraclass correlation coefficient (ICC [model 2, k]), standard error of measurement (SEM [expressed both in absolute terms and as a percentage of the mean]), and the minimal difference needed to be considered real (MD). As presented in a recent publication (Burton and Stock 2018), our laboratory's test-retest reliability statistics for rectus femoris echo intensity in college-aged females were: ICC = .928; SEM = 4.21 AU (4.22%); MD = 11.68 AU. For rectus femoris cross-sectional area, these statistics were as follows (Burton and Stock 2018): ICC = .982; SEM = 0.24 cm 2 (5.43%); MD = 0.67 cm 2 .…”
Section: Ultrasonography Test-retest Reliabilitymentioning
confidence: 61%
“…All visits to the laboratory occurred at the same time of day (± one hour) throughout the course of the study. All imaging and image analyses were performed by the same investigators utilizing methods described in our previous publications (Burton and Stock 2018;Mota et al 2017). Throughout the study, participants were asked to refrain from alcohol, keep their dietary habits consistent, and comply with the immobilization protocol.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%